Effects of project management maturity, sustainability and governance mediated by project success on corporate reputation of public sector organizations in Pakistan - Irfan, Muhammad (2018)
Since the 1960’s, practitioners and researchers are interested in the concept of reputation. A positive reputation is considered to be a competitive advantage for organizations, whereas, a negative reputation results in financial losses and distrust from the stakeholders. Research on corporate reputation has mainly focused on the corporate sector ignoring the public sector. It is because the private sector is more cautious of its reputation than the public sector. Thus, this gap has resulted in an unreliable, not sufficiently transparent, and inefficient reputation of public sector organizations. Likewise, in Pakistan, public sector does not have access to public view which limits them from realizing & establishing their own reputation. People of Pakistan have raised major concerns about negative reputation of the public sector due to its poor performance on the projects. Thus, this research aims to examine the effect of factors in projects (project governance, project management maturity, sustainability and project success) on the corporate reputation of public sector organizations in Pakistan.This study suggests a framework which can be used to create and enhance the reputation of public sector organizations. The proposed research framework was built upon the tenets of Stewardship theory, Stakeholder theory, Resource Based theory and Signaling theory. Data for the study was collected from 425 respondents across Pakistan, which included project managers, project directors, architects, project team members working on public sector projects. The data was then analyzed using partial least squares structural equation modelling (PLS-SEM). The result of these analyses confirmed that three of the proposed factors in projects (1) project management maturity, (2) sustainability, and (3) project success are significant predictors of corporate reputation. Other findings suggest that, success on projects can be achieved by project governance, project management maturity, and sustainability. Project success was also observed to significantly mediate between project governance, project management maturity, sustainability and corporate reputation. In a broader perspective, this study confirms how different factors on projects can develop and enhance reputation of public sector organizations. The managerial implications of the study are, (i) managers need to improve their success rates on projects to satisfy the public, so that ultimately the reputation of these organizations can be enhanced (ii) issues related to project success can be resolved by addressing project governance, upgrading the existing project management structures and introducing sustainable practices.